Doubling farmers’ income with potato - Rana, Rajesh K; Chakrabarti, S K; Singh, Rajbir (Indian Horticulture, 2020)
India is predominantly a farmers’ country as about half of our population derives livelihood from agriculture. However, more than two thirds of Indian farmers being small and marginal, their farm income is inadequate to meet family needs satisfactorily. Higher rate of inflation than the rate of nominal growth in farm income and tremendous enhancement in the family expenses mainly on account of children’s education and medical care have led Indian farmers into the state of financial distress and despair. As the rate of growth of farmers’ income is much slower than the rate of growth of expenses of the farm families, this financial discomfort is becoming deeper and deeper with the passage of time.